Ensuring fair treatment of investors: a novel approach for revaluation of liabilities from unissued and unredeemed investment shares in collective investment funds - Balcerzak, Adam P.; Skalický, Roman; Zinecker, Marek; Meluzín, Tomáš; Škapa, Stanislav; Pietrzak, Michał Bernard (Technological and Economic Development of Economy, 2026)
In the dynamic world of open-ended investment funds, where investors continuously enter and exit, and in funds with multiple classes of investment shares, a critical issue often goes unnoticed: the revaluation of liabilities from unissued and unredeemed shares. These liabilities, typically left unsettled and unrevalued for extended periods, can significantly skew the Net Asset Value per Share (NAVpS), leading to unfair treatment of different groups of investors. In this paper, a novel methodological framework designed to adjust the NAVpS is introduced that not only ensures fair treatment among all groups of investors, but also provides unbiased performance information to potential investors. It also addresses the complexities of non-revalued liabilities in funds with multiple investment classes, which can disrupt class allocation ratios. The practical implications of the framework are profound. The issues of fair allocation across multiple investment classes and mitigating distortions arising from unrevalued liabilities related to unissued and unredeemed shares are addressed. As demonstrated in focused case studies, these distortions can become significant, depending on the size of the liabilities and changes in the value of underlying assets. We believe that our approach contributes to a more transparent investment landscape for all stakeholders.